Frihed og kong Valdemar! – Politisk middelalderisme i Levin Christian Sanders Niels Ebbesen af Nörreriis (1797) og Malthe Conrad Bruuns ”Niels Ebbesen. Tyrandræberen” (1797) - Kjærulff, Berit (Slagmark - Tidsskrift for idéhistorie, 2019)
In the 1790s, the Danish publicity abounded with debate about freedom, republican ideas, and the Danish monarchy. This debate did not express itself as much in critique of the Crown as in terms of discursive attempts to reconcile republican ideas with the Danish absolute monarchy. In this article, it is argued that contemporary literature was an important instrument for carrying out such considerations. The article examines the use of the Danish medieval freedom fighter Niels Ebbesen to discuss the conditions of freedom under absolute rule in two pieces of literature. The article argues that Bruun’s ode “Niels Ebbesen. Tyrandræberen” (1797) dismisses the possibility of freedom under monarchy and suggests that the ode’s medievalism might have been a contributing factor in preventing legal proceedings against it (unlike other of Bruun’s state critical literature). It further argues that Sander’s drama Niels Ebbesen of Nörreriis (1797) uses medieval history to represent an ideal form of government which unites conditions for republican freedom with Danish monarchy. The overall argument is, then, that the two pieces of literature serve to unfold political considerations pertinent to the contemporary society.